ESTIMATION OF MAXIMUM ACTIVE POWER TRANSMISSION TO LOAD FOR ACTIVE MULTI-POLAR DEVICES - A. V. Bondarenko; V. I. Mojar; V. A. Ustimovich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers problems of matching irreversible multi-polar circuits loaded to active multi-polar devices because power to be transmitted is maximal under such conditions. In this case we firstly determine a multi-polar equivalent for a circuit with active elements and then the obtained relations are estimated. The proposed algorithm for calculating electric circuits with active multi-polar devices is illustrated on some examples.